The Study of Strengthening Skills in High School Chemistry Micro-Lattice Teaching - Zhang, Ziyu; Sun, Yuhang; Zhao, Wenxu; Cui, Yuhao; Sun, Lin (Advances in Social Sciences Research Journal, 2025)
At present, many chemistry normal students in China know little about strengthening skills and how to use intensive skills in teaching. However, to be a good chemistry teacher, you must master the strengthening skills. Because the appropriate and reasonable use of strengthening skills in chemistry class can focus students' attention, help students to maintain correct learning behavior, and inhibit or improve bad learning behavior. Chemistry micro-grid teaching is a practical training activity, which can effectively exercise and improve the various teaching skills of chemistry teachers or normal university students. After micro-teaching, normal university students can effectively improve and enhance their own teaching skills in a relatively short period of time. This paper introduces the research status of chemistry micro-lattice teaching and strengthening skills, briefly expounds the related concepts of chemistry micro-lattice teaching and reinforcement skills, and analyzes the individual cases of cultivating strengthening skills through chemistry micro-lattice teaching.